PLOT STRUCTURE OF THE STORIES OF ISAZON SULTAN (Scientific journal of the Fergana State University, 2026)
This article examines the storytelling mastery of the writer Isajon Sultan. It analyzes the characteristics of the short story genre and the structure of plots based on a study of his narratives. The author’s individual style is highlighted through an analysis of the plot elements in the story “Oydinbulok”. The research employs analytical, psychological, descriptive, and hermeneutic methods to reveal the intricacies of Sultan’s narrative techniques.